Schooling as a Formative Political Experience: Authority Relations and the Education of Citizens. Issue 1 (7th February 2018) - Bruch, Sarah K.; Soss, Joe
Abstract : How does formal education matter for inequalities of political behavior across the citizenry? Most answers to this question focus on the things that schools allocate, such as skills, knowledge, and resources. By contrast, we draw on policy feedback research to resuscitate a more "Deweyian" appreciation for schools as sites where citizens have their earliest formative experiences with public authority and learn what it means to participate in a rule-governed community. Using nationally representative panel data, we conduct an intersectional analysis of how race, class, and gender combine to shape student experiences with school authority relations, and estimate how these experiences are associated with later citizen dispositions in young adulthood. We find strong evidence that negative school authority experiences depress young adult political engagement and trust in government. American schools, we conclude, function as powerful sites of experiential learning that tighten the bond between social hierarchies and civic inequalities.